2023
DOI: 10.1002/ece3.9881
|View full text |Cite
|
Sign up to set email alerts
|

Exploring fishing threat at fleet segment and subregional scale: Least expert knowledge and a resilience versus disturbance‐based approach as conservation's tools for cartilaginous fish

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 120 publications
1
3
0
Order By: Relevance
“…The prevalence of juveniles and newborns of different of large pelagic sharks and rays here reported adds new insights to the environmental importance of the Asinara Gulf and Bonifacio Mouths for elasmobranchs. As recently shown, the same area exhibits also a high species diversity for the small-and medium-sized demersal sharks and skates distributed in coastal and deep grounds of the Gulf (Scacco et al, 2023b). Referring to the present sample, the bycatch of juveniles of the shortfin mako and blue sharks occurred all in the proximity of the Castelsardo Canyon, which is also the local fishing area for the target species: the swordfish X. gladius (A.G.C.I, 2009).…”
Section: Favorable Habitat and Hydrological Constraintssupporting
confidence: 57%
See 1 more Smart Citation
“…The prevalence of juveniles and newborns of different of large pelagic sharks and rays here reported adds new insights to the environmental importance of the Asinara Gulf and Bonifacio Mouths for elasmobranchs. As recently shown, the same area exhibits also a high species diversity for the small-and medium-sized demersal sharks and skates distributed in coastal and deep grounds of the Gulf (Scacco et al, 2023b). Referring to the present sample, the bycatch of juveniles of the shortfin mako and blue sharks occurred all in the proximity of the Castelsardo Canyon, which is also the local fishing area for the target species: the swordfish X. gladius (A.G.C.I, 2009).…”
Section: Favorable Habitat and Hydrological Constraintssupporting
confidence: 57%
“…On the other hand, the globally increased implementation of conservation actions in recent years seems to be inked with some signs of population recovery actually observed for a limited number of elasmobranch species, such that a green list, complementary to the IUCN red list for elasmobranchs, has been proposed (Grace et al, 2021). For Mediterranean elasmobranch species, Scacco et al (2023b) recently suggested that the severity of IUCN assessments depends on the interaction between the speciesspecific characteristics of the life history traits (Cheung et al, 2005;Cheung et al, 2007) and the variation in the intensity of the fishing threats posed by different fishing gear on different species at a given geographic scale. The aim of this work is to report on the prevalence of juveniles and newborns of endangered elasmobranchs observed in the bycatch of pelagic longlines and trammel nets of the Asinara Gulf.…”
mentioning
confidence: 99%
“…Despite the reduction in DD species obtained in the 2022-updated assessment, their number is still worryingly high on the Italian IUCN Red List. Whatever the extinction risk status of a DD species, the problem is that the DD category might hide a concerning extinction risk status for several species at both the local (33) and larger scale (20,34,35). On the other hand, a Green List, complementary to the IUCN Red List for elasmobranchs, has been proposed based on the likely link between some signs of population recovery recently observed for a limited number of elasmobranch species, and the globally increased implementation of conservation actions (36).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the Red List evaluation helps compare information on species' conservation status based on strict and replicable criteria and threats across different geographical scales. For instance, it has been recently shown that the severity of IUCN assessments for the Mediterranean elasmobranch species depends on the interaction between the species-specific characteristics of the life history traits (19) and the variation in the intensity of the fishing threat posed by different fishing gears on different species at a given geographic scale (20). In addition, the different assessment cycles allow comparison of the species extinction risk over time.…”
Section: Introductionmentioning
confidence: 99%